Experimental Study on the Improvement of the Quality of Tooth Root Surface by Vertical Cross Spindle Barreling Finishing - Nie Yong (Jixie chuandong)
The finishing process of heavy-duty gears of a kind of mine is carried out by using the vertical cross spindle gear grinding and finishing process. The processing effect of the method on the tooth root is studied emphatically. The tooth surface roughness and micro-appearance contrast is carried out. The experimental results show that the roughing process can significantly reduce the tooth surface roughness at the tooth root position,and the Ra value is reduced from 0. 7 μm to about 0. 2 μm on the basis of grinding,the roughness increased by 1 to 2 level and the Rz value is from 3. 0 μm down to about 1. 0 μm,while the tooth surface processing knife marks,microscopic defects and other basic removal. Compared with the cyclotron roller finishing method,the new technology can make the gear live better tooth surface quality.